The tortoise is an animal but he is also a wise creature - Nazareth, Peter
This article is chapter 5 of the novel by an African writer to win a major French literary award in 1968. The novel was originally written in French and published in 1968 in London
AR/SIC/1/4/13
English
Shelf no. 3
Keywords: Literature